Failure of risk assessment on ships: factors affecting seafarer practices. Issue 3 (3rd July 2019) - Ghosh, Samrat; Daszuta, Waldemar
ABSTRACT: Past analysis of marine accident investigations has revealed that inadequate risk assessment conducted on board ships lead to maritime accidents. The International Management Code for the Safe Operation of Ships and for Pollution Prevention (ISM Code) provided an international standard for the safe operation of ships with risk assessment as one of the principal precepts of the Code. However, effective implementation of the process of risk management cannot be achieved without the active involvement of competent seafarers on board ships. This paper reviewed a compilation of empirical research publications regarding ship safety to infer the possible reasons for the failure of risk assessment by focusing on areas (training and competence, procedural approach, process verification, culture and organisation) that affect seafarer practices. The findings highlighted the challenges faced by the maritime industry that warrant attention at the organisational level. The challenges were classified as: Lack of adequate training and competency in non-technical skills; Failure of a procedural approach to risk management; Risk perceptions, attitudes, and cultural/organisational factors; and Process verification: lack of ownership and identification of safety objectives.